25(OH) vitamin D suppresses macrophage adhesion and migration by downregulation of ER stress and scavenger receptor A1 in type 2 diabetes - Riek, Amy E.; Oh, Jisu; Darwech, Isra; Moynihan, Clare E.; Bruchas, Robin R.; Bernal-Mizrachi, Carlos (The Journal of steroid biochemistry and molecular biology, 2014)
•25(OH)D suppresses monocyte/macrophage adhesion to fibronectin.•25(OH)D reduces monocyte/macrophage migration induced by MCP-1.•25(OH)D downregulates monocyte ER stress protein and SR-A1 expression.•SR-A1 knockout prevents vitamin D deficiency-induced macrophage adhesion/migration.•SR-A1 knockout suppresses ER-stress-induced macrophage adhesion/migration. Cardiovascular disease (CVD) is the leading cause of mortality in patients with type 2 diabetes mellitus (T2DM). Vitamin D deficiency is not only more prevalent in diabetics but also doubles the risk of developing CVD. However, it is unknown whether 25-hydroxy vitamin D [25(OH)D3] replacement slows monocyte adhesion and migration, critical mechanisms involved in atherosclerosis progression. In this study, monocytes from vitamin D-deficient diabetic patients were cultured either in the patient's serum or in vitamin D-deficient media with or without 25(OH)D3 treatment. Adding 25(OH)D3 to monocytes cultured in vitamin D-deficient serum or media decreased monocyte adhesion to fibronectin and migration stimulated by monocyte chemotactic protein 1 (MCP-1). Accordingly, 25(OH)D3 decreased adhesion marker β1- and β2-integrin expression and migration receptor chemokine (C-C motif) receptor 2 (CCR2) expression. 25(OH)D3 treatment downregulated monocyte endoplasmic reticulum (ER) stress and scavenger receptor class A, type 1 (SR-A1) expression. The absence of SR-A1 prevented the increased macrophage adhesion and migration induced by vitamin D deficiency. Moreover, the absence of SR-A1 prevented the induction of adhesion and migration and expression of their associated membrane receptors by Thapsigargin, an ER stress inducer. These results identify cellular activation of monocyte/macrophage vitamin D signaling through 25(OH)D3 as a potential mechanism that could modulate adhesion and migration in diabetic subjects. This article is part of a Special Issue entitled ‘16th Vitamin D Workshop’.